In her sights (Rocky Mountain bounty hunters, 1, 1, 2019)
He may be her greatest rival—her sworn enemy—but when they face a hidden danger neither could survive alone, he'll soon become her partner...and fiercest protector. Bounty hunter Molly Pax fought hard for everything she has, turning the struggling family business into an unqualified success. She doesn't need complications in her life—especially not John freaking Carmondy. Six feet of pure trouble, with a cocky grin to match, John's the most cheerfully, annoyingly gorgeous frenemy Molly's ever had the pleasure of facing...and he may be her only hope of making it past these dangerous grounds alive. John's been over the moon for Molly for years, but she's always seemed untouchable. Unreachable. Now she's looking to him for help, and he'll be damned if he lets her and her sisters down. Teaming up against nearly impossible odds, they'll fight to make it through this alive...even if it means learning to trust in a connection that burns brighter than either has ever known. Get out your trusty handcuffs: This pulse-pounding romantic suspense contains sizzling enemies-to-lovers attraction, long-time pining, explosions and explosive chemistry between two rival bounty hunters, and a family bond that'll have you coming back for more. This is the first book in Katie Ruggle's Rocky Mountain Bounty Hunter series.

Third son's a charm (Survivors (Shana Galen), 1, 1, 2017)
Ewan Mostyn thinks a job as a duke's daughter's bodyguard will be easy—but Lady Lorraine has a few tricks up her sleeve that spark an undeniable passion. "I know we aren't suited. You are silent, and I speak all the time. You're a younger son with no fortune or title, and I'm the daughter of a duke. You are a brave war hero, and I've never done anything of any note. But I cannot seem to help how I feel when we are together. You are the only true thing in my life. Don't you see? Everything else is a diversion." Fiercely loyal to the survivor's club that make up his friends and comrades, Ewan Mostyn is the toughest in a group of younger sons of nobility who met as soldiers and are now trying desperately to settle back into peaceful Society. Ewan trusts his brawn more than his brains, but when he's offered a job watching the Duke of Ridlington's stubbornly independent daughter, he finds both are challenged. Lady Lorraine wants none of her father's high-handed ways, and she'll do everything in her power to avoid her distressingly attractive bodyguard—until she lands herself in real trouble. Lorraine begins to see Ewan's protectiveness in a new light, and she can only hope that her stoic guardian will do for her what he's always done—fight for what he wants. Praise for Shana Galen's Regency Romance Third Son's a Charm: "Shana Galen's deliciously brooding hero and delightfully quirky heroine turn this tale of adventure into an endearing love story that kept me up all hours reading... Wonderful!"—SABRINA JEFFRIES, New York Times bestselling author "Shana Galen delivers again!... A sharp, poignant battle of wills between a wonderful wounded hero and the only heroine brave enough to get past his defenses. Don't miss it!"—EILEEN DREYER, New York Times bestselling author "Galen charms readers with poignant and unforgettable characters, humor, and a passionate page-turning tale that's impossible to put down"—LORRAINE HEATH, New York Times and USA Today bestselling author

Run to ground (Rocky Mountain K9 Unit, 1, 1, 2017)
I lost my mentor, my K9 partner, and damn near my will to live. But when a ruthless killer targets a woman on the run, I'll do whatever it takes to save her. Still grieving over too many losses in my life, I've got no room for more distractions. But though my instincts scream to keep my distance from Jules Jackson, I can't seem to stay away. It doesn't help that my new K9 companion has fallen head over paws for Jules's rambunctious family. Or that when I'm with her, I finally feel peace. In the heart of the beautifully rugged Colorado Rockies, Jules offers me a safe place to land, and to heal. With her warmth and compassion, it's no mystery why my K9 can't live without her either. But neither of us were prepared for the dangerous threat lurking so close to home... And this time, there's no escape. What People Are Saying about Katie Ruggle's Rocky Mountain K-9 Unit Series: "Gripping suspense, unique heroines, sexy heroes."—CHRISTINE FEEHAN, #1 New York Times Bestselling Author "I love Ruggle's characters. They're sharply drawn, and vividly alive. I'm happy when they find each other. These are wonderful escapist books."—CHARLAINE HARRIS, #1 New York Times Bestselling author of the Sookie Stackhouse series "Sexy and suspenseful, I couldn't turn the pages fast enough."—JULIE ANN WALKER, New York Times and USA Today Bestselling Author, for Hold Your Breath "Chills and thrills and a sexy slow-burning romance from a terrific new voice."—D.D. AYRES, author of the K-9 Rescue Series, for Hold Your Breath

An affair with a spare (Survivors (Shana Galen), 3, 1, 2018)
"An endearing love story that kept me up all hours reading... Wonderful!" —SABRINA JEFFRIES, New York Times bestselling author, for Third Son's a Charm He's turned seduction into an art form... Rafe Beaumont, fifth son of an earl, uses his irresistible charm with the ladies to glean dangerous war secrets. Now he's putting those skills to the ultimate test: capturing an elusive assassin by seducing his daughter. The problem? She's entirely immune to Rafe's flattery. Never before has Collette Fortier met a man as attractive as Rafe. But her father's life is at stake, and succumbing to Rafe would be disastrous. But when Rafe turns the tables on her, offering support and friendship instead of a fleeting affair, Collette finds herself tempted in ways she never could have imagined... "Bright, funny, poignant, and entertaining—everything historical romance fans could ask for." —Kirkus Reviews Starred Review for No Earls Allowed The Survivors Series: Third Son's a Charm (Book 1) No Earls Allowed (Book 2) An Affair With a Spare (Book 3) What People Are Saying About Shana Galen: "Shana Galen charms readers with poignant and unforgettable characters, humor, and a passionate page-turning tale that's impossible to put down... Galen is an amazing talent and never disappoints." —Lorraine Heath, New York Times and USA Today bestselling author, for Third Son's a Charm "Shana Galen delivers again!...A sharp, poignant battle of wills between a wonderful wounded hero and the only heroine brave enough to get past his defenses. Don't miss it!" —Eileen Dreyer, New York Times bestselling author, for Third Son's a Charm

Fuel for fire (Black Knights Inc, 9, 1, 2017)
A USA Today Bestseller! A brooding covert operative and a spunky CIA agent discover a burning passion in the next installment of Julie Ann Walker's red-hot BKI series Dagan Zoelner has made three huge mistakes The first two left blood on his hands. The third left him wondering...what if? What if he had told the woman of his dreams how he felt before his world fell apart? Spitfire CIA agent Chelsea Duvall has always had a thing for bossy, brooding Dagan. It's just as well that he's never given her a second look, since she carries a combustible secret about his past that threatens to torch their lives... "The heat between the hero and heroine is hotter than a firecracker lit on both ends... Readers are in for one hell of ride!" —RT Book Reviews for Hell for Leather 4½ Stars

The convenient marriage (Regency Romances, ,, 2009)
Discover the Regency romance writer all your favorite authors adore: "You're in for a treat." —NORA ROBERTS "One of the great protagonists of the historical novel." —PHILIPPA GREGORY "She's the original." —JULIA QUINN "Georgette Heyer created a genre so rich that thousands of us have been mining it ever since."—LORETTA CHASE "No one has ever matched Georgette Heyer for charm and wit."—LISA KLEYPAS "Georgette Heyer's legacy is a gift to all of us who love the Regency period."—LORRAINE HEATH "Georgette Heyer's Regency romances are my perennial favorites!"—LENORA BELL Horatia Winwood is simply helping her family. When the Earl of Rule proposes marriage to her sister Lizzie, Horatia offers herself instead. Her sister is already in love with someone else, and Horatia is willing to sacrifice herself and tell a few convenient lies for her family's happiness. Everyone knows she's no beauty, but she'll do her best to keep out of the Earl's way and make him a good wife. And then the Earl's archenemy, Sir Robert, sets out to ruin her reputation... The Earl of Rule has found just the wife he wants. Unbeknownst to Horatia, the Earl is enchanted by her. There's simply no way he's going to let her get into trouble. Overcoming some misguided help from Horatia's harebrained brother and a hired highwayman, the Earl routs his old enemy, and wins over his young wife—proving theirs was no accidental marriage and gifting her with a love that she never thought she could expect.

An inconvenient duke (Lords of the Armory, 1, 1, 2019)
A steamy feminist Regency romance from acclaimed author Anna Harrington. All's fair in war...and in love... "We all make mistakes." His sensuous lips twisted in amusement, and he murmured a bit too huskily for comfort, "Didn't feel like a mistake to me." He kept his gaze locked onto hers as he raised the glass to take a sip. "We kissed last night, and I strongly suspect that we both want to do it again." His head tilted slightly as he studied her. "If I came around this desk and took you into my arms, would you stop me?" Marcus Braddock, former general and newly appointed Duke of Hampton, is back from war. Now, not only is he surrounded by the utterly unbearable ton, he's mourning the death of his beloved sister, Elise. Marcus believes his sister's death wasn't an accident, and he's determined to learn the truth—starting with Danielle Williams, his sister's beautiful best friend. Danielle is keeping deadly secrets of her own. She has dedicated her life to a charity that helps abused women—the same charity Elise was working for the night she died. When Danielle's work puts her life in danger, Marcus comes to her rescue. But Danielle may not be the one in need of rescuing... Praise for Anna Harrington: "As steamy as it is luscious. My favorite kind of historical!"—GRACE BURROWES, New York Times bestselling author, for Dukes Are Forever "Enchanting...Harrington combines suspenseful mystery and charming romance in this compulsively readable treat."—Publishers Weekly STARRED REVIEW "A touching and tempestuous romance, with all the ingredients Regency fans adore."—GAELEN FOLEY, New York Times bestselling author, for Dukes Are Forever

No earls allowed (Survivors (Shana Galen), 2, 1, 2018)
It is a truth universally acknowledged that a lady can do anything a man can do: backwards and in high-heeled dancing slippers. Lady Juliana, daughter of the Earl of St. Maur, needs all the help she can get. She's running a ramshackle orphanage, London's worst slumlord has illicit designs on her, and her father has suddenly become determined to marry her off. Enter Major Neil Wraxall, bastard son of the Marquess of Kensington, sent to assist Lady Juliana in any way he can. Lucky for her, he's handy with repairs, knows how to keep her and the orphans safe, and is a natural leader of men. Unfortunately for both of them, the scandal that ensues from their mutual attraction is going to lead them a merry dance... The Survivors Series: Third Son's a Charm (Book 1) No Earls Allowed (Book 2) An Affair With a Spare (Book 3) Praise for Third Son's a Charm: "Shana Galen's deliciously brooding hero and delightfully quirky heroine turn this tale of adventure into an endearing love story that kept me up all hours reading....Wonderful!"—Sabrina Jeffries, New York Times bestselling author "Shana Galen delivers again!...A sharp, poignant battle of wills between a wonderful wounded hero and the only heroine brave enough to get past his defenses. Don't miss it!" —Eileen Dreyer, New York Times bestselling author "Shana Galen charms readers with poignant and unforgettable characters, humor, and a passionate page-turning tale that's impossible to put down... Galen is an amazing talent and never disappoints."—Lorraine Heath, New York Times and USA Today bestselling author

In safe hands (Search and rescue (Katie Ruggle), 4, 1, 2017)
When recluse Daisy Little witnesses a terribe crime that may implicate a member of the Search & Rescue squad, it's up to Sheriff Chris Jennings to keep her safe, even if it means turning against one of his own.

The duke knows best (Duke's sons, 5, 1, 2017)
They're wrong for each other, for all the right reasons... Lord Randolph Gresham has come to London for one reason only—to find a suitable wife. Verity Sinclair may be intelligent, beautiful, and full of spirit, but her father knows a secret about Randolph that makes her entirely unsuitable as his bride. Not right for him at all, never, not a chance. Verity knows that Lord Randolph lives in a country parish, and she wants nothing more than to escape to town. He may be fascinating, attractive, rich, and the son of a duke, but she'll never marry him, nor will she talk to him, flirt with him, walk with him, or dine with him. She'll sing a duet with him, but only this one time, and only because everyone insists. But one duet invariably leads to another. The Duke's Sons Series: Heir to the Duke (Book 1) What the Duke Doesn't Know (Book 2) Lord Sebastian's Secret (Book 3) Nothing Like a Duke (Book 4) The Duke Knows Best (Book 5)

Powder and patch (Thorndike Press large print clean reads, ,, 2008)
When Cleone Charteris returns from finishing school, she is determined to attract the attentions of Philip Jettan, her childhood friend.

The Darcys & the Bingleys: a tale of two gentlemen's marriages to two most devoted sisters (The Darcys & the Bingleys, 1, 1, 2008)
Description Not Provided

Joy to the wolves (Red wolf, 1, 1, 2020)
When she inherits an antique shop in Portland, Oregon, right before the holidays, red wolf shifter Brooke Cerise is drawn into a kidnapping case and becomes the prime suspect of the far-too-intriguing shifter Detective Josh Wilding.

The new girl (Tantor Media, Inc., Sourcebooks, Sourcebooks Fire, 2022)
A transfer student and scholarship recipient, sophomore Lia Setiawan is angered when she discovers a cheating ring, but by the time she finds a dead body and shuts down the campus drug dealer, she fears she might be the biggest snake in the Draycott Academy nest of vipers.

Survive the night (Rocky Mountain K9 Unit, 3, 1, 2018)
"Vivid and charming." —CHARLAINE HARRIS, #1 New York Times Bestselling Author He's always been a haven: For the lost. The sick. The injured. But when a hunted woman takes shelter in his arms, this gentle giant swears he'll do more than heal her battered spirit—he'll defend her with his life. K9 Officer Otto Gunnersen always had a soft spot for anyone in need. As Monroe's very own Dr. Doolittle, he dedicates himself to rehabilitating the injured souls that cross his path—but for all his big heart, he's never been in love. Until he meets Sarah Clifton's haunted eyes. Until he realizes he'll do anything to save her. All Sarah wants is to escape a life caught between ambitious crime families, but there's no outrunning her past. Her power-mad brother would hunt her to the ends of the earth...but he'd never expect Sarah to fight back. With Otto and the whole of Monroe, Colorado by her side, Sarah's finally ready to face whatever comes her way. It's time to take a stand. "Gripping suspense, unique heroines, sexy heroes." —CHRISTINE FEEHAN, #1 New York Times Bestselling Author Rocky Mountain K-9 Unit Series: Run to Ground (Book 1) On the Chase (Book 2) Survive the Night (Book 3) Through the Fire (Book 4) What People Are Saying About Romantic Suspense by Katie Ruggle: "I love Ruggle's characters. They're sharply drawn, and vividly alive. I'm happy when they find each other. These are wonderful escapist books." —CHARLAINE HARRIS, #1 New York Times Bestselling author "Sexy and suspenseful, I couldn't turn the pages fast enough." —JULIE ANN WALKER, New York Times and USA Today Bestselling author for Hold Your Breath "Chills and thrills and a sexy slow-burning romance from a terrific new voice." —D.D. AYRES, author of the K-9 Rescue Series for Hold Your Breath

Through the fire (Rocky Mountain K9 Unit, 4, 1, 2018)
"Vivid and charming."—CHARLAINE HARRIS, #1 New York Times bestselling author of the Sookie Stackhouse series He's tall. He's dark. He's brutally handsome... And he may be her only hope. Kit Jernigan despairs of ever fitting in with her new tight-knit K9 unit—they've been through too much to welcome a stranger. So when a killer strikes, it's a fight to convince her fellow officers to trust her long enough to catch the woman she knows is responsible. She can't do it on her own. What she needs most is a partner: local fire spotter Wesley March. Wes knows in his heart that Kit is right, and he's willing to leave his lonely tower to help her prove it. But the more time they spend together, the hotter the fire smolders...and the more danger they're in. A member of the K9 unit's inner circle is determined to have her revenge—no matter who gets burned in the process. This time, it's personal. "Gripping suspense, unique heroines, sexy heroes." —CHRISTINE FEEHAN, #1 New York Times Bestselling Author Rocky Mountain K-9 Unit Series: Run to Ground (Book 1) On the Chase (Book 2) Survive the Night (Book 3) Through the Fire (Book 4) What People Are Saying about Katie Ruggle's Romantic Suspense: "I love Ruggle's characters. They're sharply drawn, and vividly alive. I'm happy when they find each other. These are wonderful escapist books."—CHARLAINE HARRIS, #1 New York Times Bestselling author of the Sookie Stackhouse series "Sexy and suspenseful, I couldn't turn the pages fast enough."—JULIE ANN WALKER, New York Times and USA Today Bestselling Author for Hold Your Breath "Chills and thrills and a sexy slow-burning romance from a terrific new voice."—D.D. AYRES, author of the K-9 Rescue Series for Hold Your Breath

Black sheep (Sourcebooks Inc, Sourcebooks, 2008)
Abigail Wendover, on the shelf at 28, is kept busy when her niece falls head over heels in love with a handsome fortune hunter and Abbie is forced into a confrontation with his scandalous uncle. Miles Calvery is the black sheep of his family- enormously rich from a long sojourn in India, disconcertingly blunt and brash. But he turns out to be Abbie's most important ally in keeping her niece out of trouble. But how can he possibly be considered eligible when she has worked so hard to rebuff his own nephew's suit for her niece? And how can she possibly detach from an ailing sister who needs her? This is a heroine who has to be, literally, swept off her feet...

Illegal (Illegal, ,, 2018)
A powerfully moving, award-winning graphic novel that explores the current plight of undocumented immigrants from New York Times bestselling author Eoin Colfer and the team behind the Artemis Fowl graphic novels. How can a human being be illegal for simply existing? Ebo is alone. His brother, Kwame, has disappeared, and Ebo knows it can only be to attempt the hazardous journey to Europe, and a better life—the same journey their sister set out on months ago. But Ebo refuses to be left behind in Ghana. He sets out after Kwame and joins him on the quest to reach Europe. Ebo's epic journey takes him across the Sahara Desert to the dangerous streets of Tripoli, and finally out to the merciless sea. But with every step he holds on to his hope for a new life, and a reunion with his family. An achingly poignant tale for learning about immigration and current global issues. This book is fiction, but it is based on a very real and terrible journey. There are young people who have lived this, and it is a story those young people want us to know about. 2019 Excellence in Graphic Literature Award Winner A New York Public Library Best Book of 2018 A Chicago Public Library Best Book of 2018 An Amazon Best Book of 2018 A Kirkus Reviews Best Middle Grade Graphic Novel of 2018 An American Library Association Notable Book for 2019 2019 YALSA Top Ten Great Graphic Novels for Teens 2019 CBC Notable Social Studies Book A Junior Library Guild Selection